Myricetin 3-O-β-D-Galactopyranoside Exhibits Potential Anti-Osteoporotic Properties in Human Bone Marrow-Derived Mesenchymal Stromal Cells via Stimulation of Osteoblastogenesis and Suppression of Adipogenesis - Fatih Karadeniz; Jung Hwan Oh; Hyun Jin Jo; Youngwan Seo; Chang-Suk Kong (Cells, 2021)
Natural bioactive substances are promising lead compounds with beneficial effects on various health problems including osteoporosis. In this context, the goal of this study was to investigate the effect of myricetin 3-O-β-D-galactopyranoside (M3G), a glycoside of a known bioactive phytochemical myricetin, on bone formation via osteogenic differentiation of human bone marrow-derived mesenchymal stromal cells (hBM-MSCs). The hBM-MSCs were induced to differentiate into osteoblasts and adipocytes in the presence or absence of M3G and the differentiation markers were analyzed. Osteoblastogenesis-induced cells treated with M3G exhibited stimulated differentiation markers: cell proliferation, alkaline phosphatase (ALP) activity, and extracellular mineralization. In terms of intracellular signaling behind the stimulatory effect of M3G, the expression of RUNX2 and osteopontin transcription factors were upregulated. It has been shown that M3G treatment increased the activation of Wnt and BMP as a suggested mechanism of action for its effect. On the other hand, M3G treatment during adipogenesis-inducement of hBM-MSCs hindered the adipogenic differentiation shown as decreased lipid accumulation and expression of PPARγ, SREBP1c, and C/EBPα, adipogenic transcription factors. In conclusion, M3G treatment stimulated osteoblast differentiation and inhibited adipocyte differentiation in induced hBM-MSCs. Osteoblast formation was stimulated via Wnt/BMP and adipogenesis was inhibited via the PPARγ pathway. This study provided necessary data for further studies to utilize the therapeutic potential of M3G against osteoporosis via regulation of bone marrow stromal cell differentiation.